Creativity and Critical Thinking - Padget, Steve (Teaching contemporary themes in secondary education., 2012)
What do we mean by creativity? What is the link between creativity and critical thinking? How can creativity and critical thinking be incorporated into classroom practice and what are the benefits for students?Creativity and critical thinking are central to effective teaching and learning and have a significant impact on students' attainment, engagement, attendance and behaviour. This book draws on recent research and policy to provide teachers with a clear framework for understanding creativity and critical thinking and practically demonstrates how they can be incorporated into clas.